2012
DOI: 10.2485/jhtb.21.245
|View full text |Cite
|
Sign up to set email alerts
|

Bone Quality of the Femoral Mid-Shaft of Ovariectomized Rats Fed a Low-Mineral Diet

Abstract: Ovariectomized (OVX) rats are accepted models for screening potential therapeutic agents for osteoporosis. A low-mineral diet accelerates bone loss in OVX rats. This study aimed to determine changes in bone quality caused by ovariectomy or by combined ovariectomy and a mineral-deficient diet. Forty-eight female Wistar rats, aged 19 weeks, were distributed into 3 groups (n = 16 per group): Group 1: (control) subjected to a sham operation and administered a normal diet, Group 2: OVX rats fed a normal diet, and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The present study using rats demonstrates the effects of estrogen deficiency (ovariectomy) alone or combined with SD on bone quality (density and strength) as assessed by 3D-mapand the 3-point bending test. The analytical system employing micro-CT and TRI/3D used in this study is capable of 3D visualization of the bone structure, qualitative analysis by pseudocolor rendering, and quantitative analysis of BMD [7][8][9]. In conventional micro-CT imaging, black and white images are evaluated because the color intensity representing X-ray penetration and non-penetration through materials is judged.…”
Section: Discussionmentioning
confidence: 99%
“…The present study using rats demonstrates the effects of estrogen deficiency (ovariectomy) alone or combined with SD on bone quality (density and strength) as assessed by 3D-mapand the 3-point bending test. The analytical system employing micro-CT and TRI/3D used in this study is capable of 3D visualization of the bone structure, qualitative analysis by pseudocolor rendering, and quantitative analysis of BMD [7][8][9]. In conventional micro-CT imaging, black and white images are evaluated because the color intensity representing X-ray penetration and non-penetration through materials is judged.…”
Section: Discussionmentioning
confidence: 99%
“…OVX groups reportedly show greater bone resorption than bone formation due to reduced estrogen secretion, leading to decreased BMD and bone strength 9) . However, although the HMD group was also exposed to an environment that reduces estrogen secretion, SMIs were higher in the HMD group than in the NMD group.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Osteoporosis is a systemic disease that results in reduced bone mass and poor trabecular bone structure. 11,12) It is defined as "a skeletal disorder characterized by compromised bone strength predisposing to an increased risk of fracture".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern of recognition by a multidisciplinary variety of funding sources endured and continued to produce strong findings. A 2012 investigation, co-funded by the NIH, National Institute of Arthritis and Musculoskeletal and Skin Disease (NIAMS), and the Ministry of Education, Culture, Sports, Science, and Technology of Japan, Suzuki et al (2012) reported dietary estrogen contributed to bone loss and were supported by later investigations (Nakada et al, 2011). As such, LeGeros was attracting multidisciplinary funding from international sources.…”
mentioning
confidence: 99%